The role of clinical parameters and cathepsin S gene expression in predicting the development of postoperative pain in patients with hip osteoarthritis - E. V. Chetina; K. E. Glemba; G. A. Markova; A. P. Prizov; M. A. Makarov (Современная ревматология, 2023)
Objective: to evaluate the significance of clinical indicators, expression of pain syndrome genes cathepsin S and pro-inflammatory cytokines in peripheral blood for predicting the development of postoperative pain (POP)  in patients with hip osteoarthritis (HOA) before total arthroplasty (TA).Material and methods. The study included 31 patients with stages III–IV of HOA (mean age 61.3±9.8 years) who underwent TA and 26 healthy volunteers (control group). Depending on the presence or absence of POP,  patients were divided into two subgroups: with POP (1st subgroup, n=12) and without POP (2nd subgroup, n=19). Patients were examined before and 6  months after surgery.Prior to TA, the level of pain was determined in all patients using the visual analogue scale (VAS), as well as using the DN4 and PainDETECT neuropathic pain questionnaires. Functional status was assessed by the WOMAC index. The development of POP ≥30 mm according to VAS was assessed 6 months after TA.Total RNA was isolated from whole blood and used to evaluate gene  expression for cathepsin S, interleukin 1 (IL1 ), tumor necrosis factor α (TNFα), and cyclooxygenase 2 (COX2) by quantitative real-time polymerase chain  reaction. Results and discussion. Complaints of pain persisted in 12 (38.7%) patients 6 months after TA. Before surgery, the expression of cathepsin S, IL1 , TNFα, and COX2 genes was significantly higher in patients of both subgroups compared to healthy controls. In addition, in patients with POP who were not satisfied with the outcome of TA, the rates of neuropathic pain according to  the DN4 questionnaire and cathepsin S gene expression were significantly  higher than in other patients. At the same time, there was no significant  difference in the expression of genes of pro-inflammatory cytokines in  patients of the studied subgroups before TA.Conclusion. The development of POP in patients with HOA may be partially associated with its perception mechanisms disturbance, and an increase in the expression of the cathepsin S gene in the peripheral blood prior to TA can serve as its prognostic biomarker.